Biology of Podisus nigrispinus preying on Alabama argillacea caterpillars in field - Oliveira, José Eudes Moraes de; Torres, Jorge Braz; Carrano-Moreira, Alberto Fábio; Ramalho, Francisco de Sousa (Pesquisa Agropecuaria Brasileira, 2002)
Nymphal development, reproduction and predation rate of Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) deprived of prey or preying upon Alabama argillacea (Huebner) (Lepidoptera: Noctuidae) were studied on cotton plants in field. Nymph and adult bugs were isolated by an organdie bag attached on cotton leaf and were deprived of prey or fed with two caterpillars of 70±10 mg every 1, 3 and 6 days. After the third instar the developmental time was delayed with food intervals. Nymphs deprived of prey reached the third instar with 16.7% survivorship, but 100% died at this stage. Nymphs feeding either daily or every three days showed survivorship superior to 60% and higher than those fed every six days. Predation of A. argillacea available daily was 12.7 and 13.2 caterpillars per nymphs when originated males and females, respectively. Additionally, females of P. nigrispinus preyed in mean 54.7 caterpillars. Females fed daily showed higher fecundity but pre-oviposition, reproductive and longevity periods were similar to the other feeding intervals. The dairy predation rate for nymphs and adults was 0.7 and 1.1 caterpillars per day; thus the availability of two caterpillars per day was in excess. The nymphal development and reproduction of P. nigrispinus were affected by food availability at three and six day's intervals.